HOMESTEAD FRUIT SPECIES DIVERSITY IN THE HAOR AREA OF BANGLADESH - Islam, M. S.; Haque, M. M.; Mannan, M. A. (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Diversity of fruit species, species richness and relative prevalence of species were investigated in the Haor area of Bangladesh. A total of 27 fruit species belonging to 19 families were identified. Among 27 fruit species, coconut, mango and jujube were found in the 100% homestead surveyed. The relative prevalence of the most common species such as banana, betel nut, coconut, mango, papaya and guava were very high while pineapple, litchi was found very low. Coconut and mango were found highly diversed (0.990) fruit species followed by guava (0.986) and papaya (0.987). It is necessary to take special attention towards the fruit production system and fruit diversity in the study areas. DOI: http://dx.doi.org/10.3329/bjpbg.v24i1.16309